Accelerator Mass Spectrometry of 14C at the Australian National University. Issue 3 (18th July 2016) - Fifield, L. K.; Allan, G. L.; Ophel, T. R.; Head, M. J.
Abstract : A 14 C measurement capability has been developed on the 14UD accelerator at the Australian National University. At present, this system operates on a medium-precision, low-throughput basis with slow cycling between isotopes. We describe unusual features of the system, and review preliminary experience with this mode of operation, in sample preparation, and with a recently installed injection system.